2017
DOI: 10.1158/1535-7163.mct-16-0591
|View full text |Cite|
|
Sign up to set email alerts
|

MALAT1 Is Associated with Poor Response to Oxaliplatin-Based Chemotherapy in Colorectal Cancer Patients and Promotes Chemoresistance through EZH2

Abstract: A major reason for oxaliplatin chemoresistance in colorectal cancer is the acquisition of epithelial-mesenchymal transition (EMT) in cancer cells. The long noncoding RNA (lncRNA), MALAT1, is a highly conserved nuclear ncRNA and a key regulator of metastasis development in several cancers. However, its role in oxaliplatin-induced metastasis and chemoresistance is not well known. In this study, we aim to investigate the prognostic and therapeutic role of lncRNA MALAT1 in colorectal cancer patients receiving oxal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
200
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(212 citation statements)
references
References 39 publications
(52 reference statements)
10
200
0
2
Order By: Relevance
“…It has been well‐formed that lncRNAs performed their cellular functions via controlling (including inhibiting or promoting) the expression of miRNAs, which in turn regulate their target genes and fulfils the actions of the whole pathways. In this study, we showed that MALAT1 interacts with DCP1A in SW480/SW620 CRC cells, which is consistent with previous research findings . Moreover, we found that enforced miR203 overexpression reversed the MALAT1 effects on CRC cell proliferation, aggression, and migration in vitro, and this process also increased the cell sensitivity to chemotherapy agents.…”
Section: Discussionsupporting
confidence: 92%
“…It has been well‐formed that lncRNAs performed their cellular functions via controlling (including inhibiting or promoting) the expression of miRNAs, which in turn regulate their target genes and fulfils the actions of the whole pathways. In this study, we showed that MALAT1 interacts with DCP1A in SW480/SW620 CRC cells, which is consistent with previous research findings . Moreover, we found that enforced miR203 overexpression reversed the MALAT1 effects on CRC cell proliferation, aggression, and migration in vitro, and this process also increased the cell sensitivity to chemotherapy agents.…”
Section: Discussionsupporting
confidence: 92%
“…Extensive efforts in the past have contributed to the understanding of both molecular and cellular mechanisms of noncoding RNAs in cancer progression, however, nearly all patients with lung cancer invariably become metastatic and chemoresistant [20]. Thus, novel molecular signatures seem to hold great promise in tumor characterization and could be used as potential prognostic markers and treatment target [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of response to chemo-resistant HCC cells, Yin et al identified 61 up-regulated and 59 down-regulated lnRNAs (fold change > 2, p < 0.05) associated with resistance [449]. Other lncRNAs identified include Linc00152 [151], SNHG5 [450], MALAT1 [451], CRNDE [452] and HULC [181]. Clearly, lncRNAs play important roles in resistance mechanisms to platinum-based drugs and could conceivably become therapeutic targets for re-sensitization strategies.…”
Section: Lncrnas Emt and Drug Resistancementioning
confidence: 99%